Population dynamics of chemotrophs in anaerobic conditions where the metabolic energy acquisition per redox reaction is limited. (21st April 2019) - Seto, Mayumi; Iwasa, Yoh
Highlight: We modeled microbial population growth based on low-energy redox reactions. More energy is extracted when the reactants are abundant and the products are rare. This "abundant resource premium" has been neglected in ecological models. Incorporating this effect leads to qualitatively new dynamics. An intermediate rate of resource acquisition maximizes the steady-state population. Abstract: We present a new model of microbial population growth that focuses on the acquisition of metabolic energy through chemosynthesis and how this depends on the concentration of resources and byproducts. Due to entropy effects, organisms extract the greater energy (i.e., they produce the greater amount of adenosine triphosphate) when they use resources that are abundant and generates byproducts that are rare. This effect, which we call the "abundant resource premium, " has been neglected in traditional models of microbial growth because the total metabolic energy acquisition is generally far greater than this premium. This term, however, cannot be neglected for many microbes, such as sulfate reducers, iron oxidizers, and methanogens, which live under conditions of low-energy availability. Our model showed qualitatively different behaviors from those observed in traditional microbial population growth models, such as the Monod model. For example, the steady-state population density was maximum at an intermediate resource-utilizing ability, suggesting that high substrate acquisition is not always advantageous for a microbial population when the availability of metabolic energy is low. We discuss possible implications for evolutionary and ecosystem sciences.